HUBUNGAN BUDAYA ORGANISASI DAN MOTIVASI KERJA DENGAN KINERJA GURU PADA SMA NEGERI SEKECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - SYAMSUL ANWAR; RR. SRI KARTIKOWATI; DAVIQ CHAIRILSYAH (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
This study aims to analyze the relationship between the variables (1) Organizationscultural with teacher performance, (2) work motivation with teachers performance, (3)Organisational culture and motivation to work together with the performance of teachers.Respondents were teachers high schools in the District Singingi Hilir Regency Kuantan amount75 Singingi the people, and the number of total population sampled or sampling teaching. Datawere collected through questionnaires intrument. Then the data were analyzed using descriptiveanalysis, inferential statistical analysis and hypothesis testing. Instrument reliability coefficientis calculated using Cronbach alpha. The results showed a positive relationship betweenorganizational culture with a performance of 0,384 teachers, and there is a positive relationshipbetween work motivation with teachers performance of 0.379. While simultaneously the resultsshowed a positive relationship between organizational culture and work motivation with teachersperformance of 0.670.